Delivery System & Techniques of Product Packing for Online Business - Iisnawati iisnawati; Dessy Yunita; Zakaria Wahab; Islahuddin Daud (Universitas Serang Raya, 2023)
Consumer behavior changes from offline to online, raise several problems that need to be faced by business actors in Kerinjing Village. These problems including complaints that occur in online sales which cause customer dissatisfaction, and the lack of knowledge of business actors in Kerinjing Village, specially in digital technology because of the level of education. Based on the survey, it is known that the most complaints that occur in online sales related to the delivery of goods. The purpose of this training is that online business actors can improve the service quality by providing knowledge about the delivery system, how to choose the right delivery service and knowing how to pack goods appropriately so that they are not damaged during shipping. The training stages start from explaining the importance of managing the delivery system, how to choose the right shipping service, managing the delivery system in e-commerce applications and practicing proper packing techniques and according to product characteristics